Sexual dysfunction and satisfaction in Kidney Transplant Patients - Mota, Renato Lains (2019)
10% of the world's population suffers from chronic kidney disease. Kidney transplants provide an improvement in the quality of life of those patients. Sexual dysfunction is common after kidney transplantation, and its etiology is presumed to be multifactorial. It has a negative impact on sexual satisfaction and health-related quality-of-life. The integration of a new organ into the body can imply an adjustment of body image, which may eventually have a negative influence on intimacy and sexual behaviors.